PERAN ORANG TUA DALAM MENINGKATKAN MINAT BELAJAR PESERTA DIDIK KELAS V DI SD NEGERI 3 SAMBIMULYO - M. Rizqon Al Musafiri; Emilka Emilka (Institut Agama Islam Darussalam Blokagung Banyuwangi, 2022)
The problems we examine in this thesis are: 1) what are the factors that affect the learning interest of class V students at SDN 3 Sambimulyo. 2) What is the role of parents in increasing the learning interest of class V students at SDN 3 Sambimulyo. In solving these problems, we conducted research using qualitative methods so that we could understand in what ways to increase the learning interest of class V students at SDN 3 Sambimulyo. The indicators used by researchers are observation, interview, data and documentation techniques. The subjects we studied were students in grade V so that the learning process went well. Researchers can collaborate with subject teachers and monitor student absences. As for the role of parents who are able to increase students' interest in learning and students become enthusiastic in learning.